Unveiling Nepali Students' Lived Experiences of ChatGPT in Secondary School Education: Opportunities and Challenges - Devkota, Mahadev (Madhyabindu Journal, 2025)
ChatGPT, a generative language model developed by OpenAI, has received global discourse regarding its transformative potential and associated challenges in educational contexts. This study examines the lived experiences and perceptions of secondary-level students in Nepal, focusing on the integration of ChatGPT within academic settings. Adopting a phenomenological research design, data were accumulated through Google Forms and semi-structured interviews with 15 purposefully sampled respondents from three distinct schools. The participants were selected based on their active use of ChatGPT in their academic activities. The findings highlight ChatGPT is viewed as a user-friendly and time-efficient cum collaborative tool, facilitating self-directed learning, enhancing vocabulary, and aiding in the exploration of complex concepts. However, participants expressed concerns regarding its accuracy, the risk of academic dishonesty, and the potential for over-reliance, which might compromise critical thinking and creativity. Additionally, participants stressed the necessity of ethical guidelines, awareness programs, and teacher training to mitigate these challenges and ensure responsible and ethical use. The study underscores the importance of thoughtful implementation of AI technologies like ChatGPT in resource-constrained academic milieus. Future research should focus on the long-term implications of AI on critical thinking, creativity, and overall educational outcomes while incorporating Key stakeholders like educators' perspectives for a comprehensive understanding of ChatGPT’s role in secondary education.